Mucus-penetrating nonviral gene vaccine processed in the epithelium for inducing advanced vaginal mucosal immune responses - Qunjie Bi; Xu Song; Yangyang Zhao; Xueyi Hu; Huan Yang; Rongrong Jin; Yu Nie (Elsevier, 2023)
Establishment of vaginal immune defenses at the mucosal interface layer through gene vaccines promise to prevent infectious diseases among females. Mucosal barriers composed of a flowing mucus hydrogel and tightly conjugated epithelial cells (ECs), which represent the main technical difficulties for vaccine development, reside in the harsh, acidic human vaginal environment. Different from frequently employed viral vectors, two types of nonviral nanocarriers were designed to concurrently overcome the barriers and induce immune responses. Differing design concepts include the charge-reversal property (DRLS) to mimic a virus that uses any cells as factories, as well as the addition of a hyaluronic acid coating (HA/RLS) to directly target dendritic cells (DCs). With a suitable size and electrostatic neutrality, these two nanoparticles penetrate a mucus hydrogel with similar diffusivity. The DRLS system expressed a higher level of the carried human papillomavirus type 16 L1 gene compared to HA/RLS in vivo. Therefore it induced more robust mucosal, cellular, and humoral immune responses. Moreover, the DLRS applied to intravaginal immunization induced high IgA levels compared with intramuscularly injected DNA (naked), indicating timely protection against pathogens at the mucus layer. These findings also offer important approaches for the design and fabrication of nonviral gene vaccines in other mucosal systems.